2020
DOI: 10.1007/s10389-020-01318-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 awareness among a group of Egyptians and their perception toward the role of dentists in its prevention: a pilot cross-sectional survey

Abstract: Aim The main purpose of the study is to assess the awareness of a group of Egyptians about COVID-19 infection and their perception of the role of dentists in its prevention. Subjects and methods An observational cross-sectional survey included 74 participants who attended Minia University Dental Hospital, Minia City, Egypt, from 10 March to 2 April 2020. A face-to-face interview using an anonymous questionnaire was carried out in this study. The questionnaire contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Creating a high level of awareness plays an important role in primary prevention and health promotion. In addition, it causes early detection of symptoms in the community [22].…”
Section: Discussionmentioning
confidence: 99%
“…Creating a high level of awareness plays an important role in primary prevention and health promotion. In addition, it causes early detection of symptoms in the community [22].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms identified comprise of fever, cough, difficulty in breathing, loss of smell, while in extreme cases can lead to pneumonia, multi-organ failure and death. 7 The rapid spread of this infection is principally through respiratory droplets of 5-10 μm in diameter, spread through the mouth or nose, when an infected person coughs or sneezes. 8 A study conducted in Singapore has identified that these droplets can be transmitted across a distance of 4.5 metres.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms identified comprise of fever, cough, difficulty in breathing, loss of smell, while in extreme cases can lead to pneumonia, multi-organ failure and death. 7 The rapid spread of this infection is principally through respiratory droplets of 5-10 μm in diameter, spread through the mouth or nose, when an infected person coughs or sneezes. 8 A study conducted in Singapore has identified that these droplets can be transmitted across a distance of 4.5 metres.…”
Section: Introductionmentioning
confidence: 99%